An Overview of Mother’s Experiences in Overcoming Speech Delay in Early Childhood - Tahani Hutrika; Ririn Muthia Zukhra; Aminatul Fitri (Indonesian Journal of Global Health Research, 2025)
Speech delay in early childhood has an impact on communication skills and long-term development. The mother's role is very important in providing stimulation because she spends the most time with the child. Each mother has a unique experience in dealing with this condition. This study aims to explore mothers' experiences in overcoming speech delay in early childhood. This study used a descriptive qualitative method with 4 participants selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using Colaizzi's thematic method. The results showed six main themes: (1) mothers' understanding of speech delay and the consultation and therapy measures taken, (2) emotional reactions in the form of rejection and sadness before accepting the child's condition, (3) stimulation efforts at home and the use of traditional medicine, (4) children's speech development varied with some showing significant improvement, (5) limited time and cost as the main obstacle, and (6) mothers' advice to other parents and therapy services. In conclusion, mothers of children with speech delay face complex emotional challenges but still try to support their children's development through various interventions. Better emotional support and access to therapy services are needed to help mothers overcome these barriers